2018
DOI: 10.1002/anie.201800319
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Dehydrogenation of N‐Heterocycles by Ternary h‐BCN Nanosheets with Visible Light

Abstract: An efficient metal-free catalytic system has been developed based on hexagonal boron carbon nitride (h-BCN) nanosheets for the dehydrogenation of N-heterocycles with visible light; hydrogen gas is released in the process, and thus no proton acceptor is needed. This acceptorless dehydrogenation of hydroquinolines, hydroisoquinolines, and indolines to the corresponding aromatic N-heterocycles occurred in excellent yield under visible-light irradiation at ambient temperature. With h-BCN as the photocatalyst and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(68 citation statements)
references
References 81 publications
1
67
0
Order By: Relevance
“…The first realization of this concept is presented, Figure . Graphitic carbon nitride (g‐CN) is a photoactive semiconductor that absorbs blue light but was rarely used for the oxygenation of organic compounds, however, dehydrogenation of N‐heterocycles was reported . Upon visible‐light irradiation we suggest that hole–electron recombination can be inhibited by the attachment of a polyoxometalate, H 3 PW 12 O 40 , to the g‐CN material; the polyoxometalate acts as an electron acceptor and shuttle.…”
Section: Figurementioning
confidence: 94%
“…The first realization of this concept is presented, Figure . Graphitic carbon nitride (g‐CN) is a photoactive semiconductor that absorbs blue light but was rarely used for the oxygenation of organic compounds, however, dehydrogenation of N‐heterocycles was reported . Upon visible‐light irradiation we suggest that hole–electron recombination can be inhibited by the attachment of a polyoxometalate, H 3 PW 12 O 40 , to the g‐CN material; the polyoxometalate acts as an electron acceptor and shuttle.…”
Section: Figurementioning
confidence: 94%
“…The acceptorless dehydrogenation of N‐heterocycles is an important reaction in organic synthesis, which also has potential in the storage of hydrogen . This reaction is usually carried out under thermal conditions, and recently shown possible to be catalyzed under visible light . The mechanism study revealed the multistep nature of the dehydrogenation process (Supporting Information, Figures S91, S92), which is suitable for the systematic study of MOFs with variable distance profiles.…”
Section: Figurementioning
confidence: 99%
“…This reaction is usually carried out under thermal conditions, and recently shown possible to be catalyzed under visible light . The mechanism study revealed the multistep nature of the dehydrogenation process (Supporting Information, Figures S91, S92), which is suitable for the systematic study of MOFs with variable distance profiles. In this study, we showed that porphyrin and porphyrin MOFs were also capable to dehydrogenate THQ under visible light.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the photocatalytic properties of semiconductors are strongly related to their crystallinity and surface properties, such as morphology, specific surface area, as well as surface feature. [33][34][35][36][37][38][39] Since the samples have similar morphological structures and specific surface areas, we explored their surface features. Herein, we investigated the atomic arrangement of the surface of BiOCl n Br 1-n .…”
Section: Mechanism Of the Alloying Effects On Improving The Photocatamentioning
confidence: 99%